Are There Non-linear Relationships between Ownership Structure and Operational Performance? Empirical Evidence from Portuguese SMEs Using Dynamic Panel Data - Pinto, António (2014)
This paper analyzes the causal relationship between the ownership concentration, insider ownership and operational performance using a sample of 4.163 Portuguese SMEs and panel data models. The main results show an endogenous and dynamic relationship between those variables. The quadratic specification established between ownership concentration and operational profitability suggests that for low levels of control rights the expropriation hypothesis prevails and for high levels the supervision hypothesis prevails. It was also possible to validate the effect of entrenchment and convergence of interests in the relationship established between the insider ownership and performance.